Eco-farming pocket - Jaballudin, Norazura; Zanuddin, Nurhazwani; Shahudin, Fakharudin (Universiti Teknologi MARA, Kedah, 2023)
At the end of 2019, the world was shaken by the emergence of a new variation virus that forced the government to run the Movement Control Order . Many of them lost their jobs and sources of income. So they began to venture into agriculture. Statistics show that agriculture has increased dramatically. However, some of them are not able to farm properly due to the seeds that germinate slowly and do not grow well. Germination is the most important stage to ensure that the tree grows well. Germination refers to the process by which an organism grows from a seed or a spore (Susan Kleatz Beal,1998) The most common forms of germination include a seed sprouting to form a seedling and the formation of a sporeling from a spore. Thus, germination occurs primarily in plant and fungal species. The EcO- Farming Pocket are designed to ensure that germination can take place successfully without causing loss to the buyer.